Meteorological data from ice-free areas in Yukidori Zawa, Langhovde and Kizahashi Hama, Skarvsnes in Sôya Coast, East Antarctica during 2009–2014 - KUDOH, Sakae; TANABE, Yukiko; UCHIDA, Masaki; IMURA, Satoshi (2015)
Fig. 1 | http://polaris.nipr.ac.jp/~parc/pub/v001/nipr_parc_187_0046.doc Table 1 | http://polaris.nipr.ac.jp/~parc/pub/v001/nipr_parc_187_0045.doc departmental bulletin paper